Accuracy of Endoscopic Diagnosis of Helicobacter pylori Based on the Kyoto Classification of Gastritis: A Multicenter Study - Zhao, Jing; Xu, Shaoxian; Gao, Yuan; Lei, Yali; Zou, Baicang; Zhou, Mimi; Chang, Danyan; Dong, Lei; Qin, Bin (Frontiers in Oncology, 2020)
Background: There is lack of clinical evidence supporting the value of the Kyoto classification of gastritis for the diagnosis of Helicobacter pylori (H. pylori) infection in Chinese patients, and there aren’t enough specific features for the endoscopic diagnosis of past infections, which is of special significance for the prevention of early gastric cancer (GC). Methods: This was a prospective and multicenter study with 650 Chinese patients. The H. pylori status and gastric mucosal features, including 17 characteristics based on the Kyoto classification and two newly-defined features unclear atrophy boundary (UAB) and RAC reappearance in atrophic mucosa (RAC reappearance) were recorded in a blind fashion. The clinical characteristics of the subjects were analyzed, and the diagnostic odds ratio (DOR), sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), area under the receiver operating characteristics curve (ROC/AUC) and 95% confidence intervals were calculated for the different features, individually and in combination. Results: For past infection, the DOR of UAB was 7.69 (95%CI:3.11-19.1), second only to map-like redness (7.78 (95%CI: 3.43-17.7)). RAC reappearance showed the highest ROC/AUC (0.583). In cases in which at least one of these three specific features of past infection was considered positive, the ROC/AUC reached 0.643. For current infection, nodularity showed the highest DOR (11.7 (95%CI: 2.65-51.2)), followed by diffuse redness (10.5 (95%CI: 4.87-22.6)). Mucosal swelling showed the highest ROC/AUC (0.726). Regular arrangement of collecting venules (RAC) was specific for no infection. Conclusions: This study provides evidence of the clinical accuracy and robustness of the Kyoto classification of gastritis for the diagnosis of H. pylori in Chinese patients, and confirms UAB and RAC reappearance partly supplement it for the diagnosis of past infections, which is of great benefit to the early prevention of GC.